2022
DOI: 10.1007/s10896-022-00485-4
|View full text |Cite
|
Sign up to set email alerts
|

The Trinidad and Tobago Covid-19 Domestic Violence Victimization and Perpetration Study

Abstract: Purpose While there is available scholarship in the Global North on DV victimization and perpetration during the COVID-19 pandemic, there is a dearth of similar scholarship in the Global South. With this in mind, the Trinidad and Tobago COVID-19 Domestic Violence Victimization and Perpetration study was conducted in an attempt to fill that void. Method An online questionnaire containing a qualitative component was used to gather data aimed at determining whether DV vict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…A survey of 602 married or cohabiting adult citizens of Trinidad and Tobago found an increase in perpetration of domestic violence (13%) and an increase in victimization of domestic violence (16%). The findings also indicated that males (17%) and females (13%) in the sample were more likely to be perpetrators of domestic violence, while males (25%) and females (12%) were more likely to be victims of domestic violence ( 6 ).…”
Section: Resultsmentioning
confidence: 88%
“…A survey of 602 married or cohabiting adult citizens of Trinidad and Tobago found an increase in perpetration of domestic violence (13%) and an increase in victimization of domestic violence (16%). The findings also indicated that males (17%) and females (13%) in the sample were more likely to be perpetrators of domestic violence, while males (25%) and females (12%) were more likely to be victims of domestic violence ( 6 ).…”
Section: Resultsmentioning
confidence: 88%